PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM MATERI PENYAJIAN DATA MATA PELAJARAN MATEMATIKA KELAS IV SDN 4 GADANG MALANG - Surya Indra Saputra, Ody; Kukuh Kuncoro, Andriyas; Dwi Ferdiani, Rosita; Sulistyo, Sulistyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary schools should ideally be active, meaningful, and student-centered, thus fostering critical thinking skills in understanding and analyzing information. However, learning conditions in grade IV of SDN 4 Gadang, Malang City, indicate that mathematics learning on data presentation is still dominated by lectures and practice exercises, resulting in students being less active in discussions, processing data, and drawing conclusions. The study subjects consisted of 29 students, consisting of 15 boys and 14 girls. Initial observations showed that boys tended to be active during discussions but were less thorough in processing data, while girls were more thorough but still lacked confidence in expressing their opinions. These conditions resulted in low student learning outcomes, with an average pre-cycle score of 45.86 and learning completion of 0%. This study aimed to improve critical thinking skills and student learning outcomes through the implementation of the Project Based Learning (PjBL) model. The study used the Classroom Action Research (CAR) method, modeled after Kemmis and McTaggart, which was implemented in two cycles. The results showed that the implementation of Project Based Learning was able to improve student learning outcomes and critical thinking skills. The average score increased to 67.24 in Cycle I and 78.45 in Cycle II, with a learning completion percentage of 89.7%. The average N-Gain of 0.63 is considered moderate. Thus, Project-Based Learning is able to create more active, collaborative, and meaningful learning, thereby optimally developing students' critical thinking skills.